Practicum conducted at the Brackishwater Aquaculture Center and Obando, Meycauayan Bulacan - Ladra, Daisy F. (College of Fisheries, University of the Philippines, 1978)
In order to feed an ever-increasing population of forty two million, large tracts of arable lands were placed under cultivation to augment the country's protein deficiency. The realization that the country's economy can still be alleviated prompted the government to introduce aquaculture in the Philippines. The historical development of aquaculture in the Philippines is probably similar to that of other Southeast Asian countries. It started from foreshore reclamation to mere trapping of fishes when the tide arises and there they are kept until big enough to be sold in the market. In instances were the land is alternatingly wet then dry, embankments are trapped inside. This is done in public communal fishing areas as well as in private lands. From this type of aquaculture techniques, fishponds expanded without the benefit of engineering competence but by mere experience of the fishermen. Designs and constructions of fishponds were therefore based on traditional techniques of trapping rather than cultivating fishes. It is a proven fact that the success and failure of a fishpond is dependent on its design and construction. It is unfortunate that aquaculture engineering is not as developed as agricultural engineering. A fishery graduate, with his basic knowledge of surveying and adequate experience can fill in this inadequacy. On the other hand, the biological and physical factors which affect fish production is known to be man. His understanding on the interplay of these factors can somehow eliminate the negative influences that deter the attainment of good fish production. This is where the full essence of the practicum lie, being in a system where there is an interplay of theories and application. My four months practicum training has brought insight to the fact that science is not more theorizing but also practical testing of the correctness of the theories undertaken. Our activities' were conducted in such a way that fieldworks were preceded by lectures. Our professors likewise, organized fieldtrips as a supplement to their intellectual limitations on the business side of aquaculture. Luckily, the fishpond operators were very accommodating to all our questions on the proper management technique to ensure good fish production.